Maternal creatine in pregnancy: a retrospective cohort study. (23rd August 2016) - Dickinson, H; Davies‐Tuck, M; Ellery, SJ; Grieger, JA; Wallace, EM; Snow, RJ; Walker, DW; Clifton, VL
Abstract : Objective: To estimate creatine concentrations in maternal plasma and urine, and establish relationships with maternal characteristics, diet and fetal growth. Design: Retrospective cohort study. Setting: Lyell McEwin Hospital, Adelaide, Australia. Population: A biobank of plasma and urine samples collected at 13, 18, 30 and 36 weeks' gestation from 287 pregnant women from a prospective cohort of asthmatic and non‐asthmatic women. Methods: Creatine was measured by enzymatic analysis. Change in creatine over pregnancy was assessed using the Friedman test. Linear mixed models regression was used to determine associations between maternal factors and diet with creatine across pregnancy and between creatine with indices of fetal growth at birth. Main outcome measures: Maternal creatine concentrations, associations between maternal factors and creatine and between creatine and fetal growth parameters. Results: Maternal smoking, body mass index, asthma and socio‐economic status were positively and parity negatively associated with maternal plasma and/or urine creatine. Maternal urine creatine concentration was positively associated with birthweight centile and birth length. After adjustment, each μ mol/l increase in maternal urinary creatine was associated with a 1.23 (95% CI 0.44–2.02) unit increase in birthweight centile and a 0.11‐cm (95% CI 0.03–0.2) increase in birth length. Conclusions: Maternal factors and fetal growth measures are associated with maternal plasma and urine creatine concentrations. Tweetable abstract: Maternal creatine is altered by pregnancy; fetal growth measures are associated with maternal creatine concentrations. Tweetable abstract: Maternal creatine is altered by pregnancy; fetal growth measures are associated with maternal creatine concentrations.